2019
DOI: 10.1248/bpb.b18-00787
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Ameliorates Chronic Renal Failure in 5/6 Nephrectomized Rats by Regulation of the mTOR/HIF-1α/VEGF Signaling Pathway

Abstract: Previous studies implicated the mammalian target of rapamycin (mTOR)/hypoxia-inducible factor-1α (HIF-1α)/vascular endothelial growth factor (VEGF) pathway in renal fibrosis and found that curcumin could suppress the expression of mTOR. Therefore, the aim of the present study was to investigate the therapeutic effects of curcumin against chronic renal failure (CRF) in a rat model induced by 5/6 nephrectomy through inhibition of mTOR/HIF-1α/VEGF signaling. A total of 70 male Sprague-Dawley rats were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A study in human kidney tubular epithelial cells (HKCs) found that curcumin exposure avoided the epithelial-to-mesenchymal transition through Akt/mTOR/p70S6K pathway inhibition [28]. In the same way, in the 5/6 nephrectomy-induced chronic kidney damage model, curcumin decreased the phosphorylation of mTOR and its targets (p70S6K and 4E-BP1) [73]. Although in both cases the study of autophagy was not the aim, the possible participation of this may be considered, since the Akt/mTOR pathway modulation is considered a classic mechanism for the regulation of autophagy [74,75].…”
Section: Protective Effects Of Curcumin Related To Autophagy Regulmentioning
confidence: 99%
“…A study in human kidney tubular epithelial cells (HKCs) found that curcumin exposure avoided the epithelial-to-mesenchymal transition through Akt/mTOR/p70S6K pathway inhibition [28]. In the same way, in the 5/6 nephrectomy-induced chronic kidney damage model, curcumin decreased the phosphorylation of mTOR and its targets (p70S6K and 4E-BP1) [73]. Although in both cases the study of autophagy was not the aim, the possible participation of this may be considered, since the Akt/mTOR pathway modulation is considered a classic mechanism for the regulation of autophagy [74,75].…”
Section: Protective Effects Of Curcumin Related To Autophagy Regulmentioning
confidence: 99%
“…Besides, curcumin improved renal fibrosis in rats by inactivating the mTOR/HIF-1α/VEGF signaling pathway (He et al, 2019). Curcumin also affected glycolysis of pancreatic cancer by inhibiting HIF-1α (Guo et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Wang et al reported that Curcumin inactivated HIF‐1α in a PGC‐1α/SirT3‐dependent manner, thereby promoting skin wound healing (Wang, Shen, et al, 2020). Besides, curcumin improved renal fibrosis in rats by inactivating the mTOR/HIF‐1α/VEGF signaling pathway (He et al, 2019). Curcumin also affected glycolysis of pancreatic cancer by inhibiting HIF‐1α (Guo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, currently, the effects of HIF and vascular endothelial growth factor (VEGF) are not well known. Some studies on renal diseases found that HIF-1 α played a protective role [ 13 15 ], but others reported that it was a risk factor [ 16 18 ]. Current evidence indicated that HIF-1 α could be regulated by some NR [ 19 21 ]; however, there was no report showing the relationship between NCOAs and HIF-1 α .…”
Section: Introductionmentioning
confidence: 99%